Math anxiety affects career choices during development - Hili Eidlin-Levy; Elad Avraham; Laurain Fares; Orly Rubinsten (SpringerOpen, 2023)
Abstract Background Links between math anxiety and the choice of a math-intensive career might change over development and differ by gender. The study included three research populations: primary school (N = 87, 48 females, mean age = 10.2), high school (N = 107, 61 females, mean age = 15.7), and university students (N = 100, 53 females, mean age = 27.4). Students completed a math anxiety questionnaire and reported their desired career choice. Results Findings suggest that math anxiety directly predicted the career choice math intensity for high school and university students, but not primary school students. Gender had a direct effect on younger students, as female students attending primary and high school preferred careers with a lower math intensity. The effect of gender on career choice math intensity for university students was not direct but mediated by math anxiety. Conclusions It is crucial to identify young students with math anxiety and provide appropriate math anxiety reduction programs to reduce the cumulative effect of math anxiety on academic achievement and career choice.